Orbital Arteriovenous Fistula Causing Only Visual Impairment due to Compression of the Optic Nerve by the Dilated Superior Ophthalmic Vein - Hirano, Yudai; Ono, Hideaki; Shojima, Masaaki; Abe, Motoo; Tanishima, Takeo; Tamura, Akira; Saito, Isamu (Asian Journal of Neurosurgery, 2023)
Orbital arteriovenous fistula (AVF) is a rare disease, and its standard therapeutic strategy has not been established. A 70-year-old male consulted an ophthalmologist due to a visual field defect in his left eye. Neurological findings showed visual impairment but no symptoms such as exophthalmos, conjunctival congestion, or diplopia. Magnetic resonance imaging showed marked dilation of the left superior ophthalmic vein (SOV). Cerebral angiography revealed an AVF that was limited to the left orbit. The feeder was a branch of the ophthalmic artery that originated from the first portion, and the drainer was the SOV, which was meandering and significantly dilated. Since the only symptom was visual impairment, the etiology was considered to be compression of the optic nerve due to a dilated SOV rather than increased venous pressure. Transvenous embolization via the facial vein was performed, and a visual field examination 1 week after the operation revealed marked improvement. Orbital AVF that develops only with visual impairment is extremely rare. As demonstrated with this case, coil embolization for proper position and reduction of the venous pressure, which relieves compression on the optic nerve, may be useful in improving the visual impairment.
Keywords: endovascular treatment; orbital arteriovenous fistula; superior ophthalmic vein; transvenous embolization; visual impairment